Frequency of Acute Ischemic Stroke among Pregnant Females - Adnan Mahmood, Muhammad Imran Khan, Sajjad Ali, Rashid Imran, Safia Bano, Muhammad Shahzad Hafeez (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Ischemic stroke during pregnancy is a rare but potentially life-threatening condition, which is essential to be recognized through the clinical signs and symptoms promptly for ensuring timely medical intervention. Objective: To determine the frequency of ischemic stroke among pregnant females. Study design: Prospective cohort study Place and duration of study: Department of Neurology, Sialkot Medical College, Sialkot from 1st January 2022 to 30th June 2023. Methodology: One thousand pregnant females were admitted in gynaecology unit and also on the post-partum females up to 42 days period were enrolled. Hospital duration was recorded inform of days. The pregnant women who were presenting clinical symptoms of ischemia stroke were assessed for confirmation through radiological imaging including MRI or CT scan. Diffusion weighted images (DWI) was used in some cases for assisting the MRI imaging. Results: The post-partum readmission had the highest risk of ischemic stroke as well as occlusion, stenosis and vascular syndromes. The overall frequency of ischemic stroke in admitted pregnant females was around 3.55% .Maximum hospital stay length was observed among pregnant females suffering from ischemic stroke. The crude and adjusted odds ratio was compared in terms of maternal age, parity, comorbidities as well as migraine. It was found that despite of maternal age >40 years the high risk factors of ischemic stroke are multifetal gestation, preeclampsia, eclampsia, migraine. Conclusion: There is a 3.55% frequency of ischemic stroke with pregnant females. The frequency increases in presence of risk factors including maternal age, multiparous, multifetal gestation, preeclampsia, eclampsia, obesity and anemia. Keywords: Frequency, Acute ischemic stroke, Pregnant females.